A pilot bedtime routine intervention for toddlers in primary care: variation by caregiver educational attainment - Mindell, Jodi A.; Lam, Joey Tsz Ying; Salih, Zainab; Heere, Megan; Williamson, Ariel A. (Frontiers in Sleep, 2026)
BackgroundA consistent bedtime routine (≥5 nights per week) is an empirically supported intervention associated with better sleep outcomes. However, few studies have examined the impacts of a bedtime routine on outcomes beyond sleep, and among families of lower educational attainment.ObjectiveThis pilot randomized controlled trial (RCT) examined initial outcomes (sleep, development, caregiver stress), feasibility, and acceptability of a primary care-based bedtime routine intervention for toddlers, and explored variation in outcomes by caregiver educational attainment.MethodCaregivers of 86 toddlers (Mage = 12.89 months, 67.4% Black/African American, 23.3% Hispanic/Latine; United States) were randomly assigned to a bedtime routine intervention or usual care at their 12-month well-child visit (age-based preventative care). At their 15- and 24-month well visits, child sleep (Brief Infant Sleep Questionnaire–R SF), social-emotional development (Brief Infant-Toddler Social and Emotional Assessment), caregiver stress (Parenting Stress Inventory-SF), and intervention acceptability were assessed.ResultsThere were no differences in outcomes between the groups, however, the intervention positively impacted sleep consolidation, social-emotional outcomes, and caregiver stress, primarily at 24 months of age, for toddlers of caregivers with lower educational attainment. Additionally, families in the intervention were more likely to include reading in their bedtime routine at 15 months. Caregivers assigned to the intervention also reported strong acceptability and 85% completed both sessions.ConclusionsThis pilot study suggests that bedtime routine intervention for toddlers is acceptable, feasible, and results in increased integration of reading at 15 months of age. Caregivers of lower educational attainment in the intervention condition reported improvements in aspects of child sleep health, social-emotional concerns, and caregiver stress, highlighting the potential for this intervention to reduce sleep health disparities. Future research should continue to examine potential bedtime routine benefits beyond sleep in larger-scale RCTs.